Toward Highly Dispersed Mesoporous Bioactive Glass Nanoparticles With High Cu Concentration Using Cu/Ascorbic Acid Complex as Precursor - Zheng, Kai; Kang, Jeonil; Rutkowski, Bogdan; Gawȩda, Magdalena; Zhang, Jue; Wang, You; Founier, Niklas; Sitarz, Maciej; Taccardi, Nicola; Boccaccini, Aldo R. (Frontiers in Chemistry, 2019)
Copper (Cu) ions have a variety of advantageous biological functionalities, such as proangiogenic and bactericidal activities. Given the intrinsic biodegradability and biocompatibility, silicate-based mesoporous bioactive glass nanoparticles (MBGNs) are considered as promising platforms for the delivery of Cu ions. However, effective incorporation of Cu into MBGNs still faces challenges, e.g., particle aggregation, the formation of insoluble crystalline Cu-based nanoparticles, and a low loading amount of Cu. We report a novel method to synthesize chemically homogenous and highly dispersed Cu-containing MBGNs (Cu-MBGNs) with tunable Cu concentration by using ascorbic acid/Cu complexes as the precursor of Cu in a microemulsion-assisted sol-gel approach. Cu-MBGNs exhibited a sphere-like shape with a particle size between 100 and 300 nm while their pore size varied from 2 to 10 nm. The inclusion of Cu, regardless of the incorporated concentration, did not significantly affect the morphology of particles. ICP-AES results indicated that the concentration of Cu in the particles could be conveniently tuned from 0 to ~6 mol% by controlling the amount of ascorbic acid/Cu complexes added, while the formation of crystalline Cu-based nanoparticles was avoided. The amorphous feature of Cu-MBGNs was proved by XRD, while the predominant oxidation state of Cu was evidenced to be Cu2+ by XPS. The incorporation of Cu did not inhibit the apatite-forming ability (bioactivity) of the particles in contact with simulated body fluid. Cu-MBGNs exhibited the capability of releasing Cu, Si, and Ca ions over time in the physiological fluid. The concentration of released Cu ions could be controlled by selecting specific Cu-MBGNs of different Cu contents. The dissolution products of most Cu-MBGNs at the dosage of 1, 0.1, and 0.01 mg/mL did not exhibit cytotoxicity, while only 7Cu-MBGN was cytotoxic at the dosage of 1 mg/mL. This study provided a feasible strategy to synthesize highly dispersed amorphous Cu-MBGNs with high Cu concentrations for biomedical applications. The particles exhibited great potential as building blocks for developing 3D scaffolds, coatings, and drug carriers, particularly for which a large amount of particles incorporated may compromise the properties of matrix materials while a relatively high concentration of released Cu ions is still required.